2022
DOI: 10.7554/elife.75720
|View full text |Cite
|
Sign up to set email alerts
|

The inherent flexibility of receptor binding domains in SARS-CoV-2 spike protein

Abstract: Spike (S) protein is the primary antigenic target for neutralization and vaccine development for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It decorates the virus surface and undergoes large motions of its receptor binding domains (RBDs) to enter the host cell. Here, we observe Down, one-Up, one-Open, and two-Up-like structures in enhanced molecular dynamics simulations, and characterize the transition pathways via inter-domain interactions. Transient salt-bridges between RBDA and RBDC a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 90 publications
(178 reference statements)
2
42
1
Order By: Relevance
“…Computer simulations provided important atomistic and mechanistic advances into understanding the dynamics and function of the SARS-CoV-2 S proteins [45-57]. All-atom MD simulations of the full-length SARS-CoV-2 S glycoprotein embedded in the viral membrane, with a complete glycosylation profile, were performed by Amaro and coworkers, providing an unprecedented level of detail about the conformational landscapes of the S proteins in the physiological environment [45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer simulations provided important atomistic and mechanistic advances into understanding the dynamics and function of the SARS-CoV-2 S proteins [45-57]. All-atom MD simulations of the full-length SARS-CoV-2 S glycoprotein embedded in the viral membrane, with a complete glycosylation profile, were performed by Amaro and coworkers, providing an unprecedented level of detail about the conformational landscapes of the S proteins in the physiological environment [45].…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations of the S-protein in solution and targeted simulations of conformational changes between the open and closed forms revealed the key electrostatic interdomain interactions mediating the protein stability and kinetics of the functional spike states [56]. Using the replica-exchange MD simulations with solute tempering of selected surface charged residues, the conformational landscapes of the full-length S protein trimers were investigated, unveiling previously unknown cryptic pockets and the meta-stable intermediate states [57]. A number of computational studies employed atomistic simulations and binding energy analysis to examine the interactions between the S-RBD Omicron and the ACE2 receptor [58-62].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Dokainish et al. [ 52 ] described the opening of RBD by adopting the new generalized replica exchange method with solute tempering of selected surface charged residues (gREST_SSCR), an enhanced method derived from generalized replica exchange with solute tempering (gREST). [ 53 ] In this study, a selection of charged residues at the RBD interface was regarded as the solute region for gREST, exploring a range of temperatures while the solvent was kept at a constant temperature.…”
Section: Molecular Dynamics Simulations To Explore Rare S Conformatio...mentioning
confidence: 99%
“…Computer simulations provided important atomistic and mechanistic insights into understanding the dynamics and function of the SARS-CoV-2 glycoproteins. Molecular dynamics (MD) simulations of the SARS-CoV-2 S proteins and mutants detailed conformational changes and diversity of ensembles, demonstrating enhanced functional and structural plasticity of the S proteins [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. All-atom MD simulations of the full-length SARS-CoV-2 S glycoprotein embedded in the viral membrane, with a complete glycosylation profile, were performed by Amaro and coworkers, providing an unprecedented level of detail about the conformational landscapes of the S proteins in the physiological environment [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations of the S-protein in solution and targeted simulations of conformational changes between the open and closed forms revealed the key electrostatic interdomain interactions mediating the protein stability and kinetics of the functional spike states [ 64 ]. MD simulations characterized the conformational landscapes of the full-length S protein trimers detailing conformational transitions between functional states and unveiling previously unknown cryptic pockets [ 65 ]. Our studies revealed that the SARS-CoV-2 S protein can function as an allosteric regulatory machinery that can exploit the intrinsic plasticity of functional regions controlled by stable allosteric hotspots to modulate specific regulatory and binding functions [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%